The Effect of Destination Image, Tourist Attractions, Facilities, Service Quality, and Promotion on Visitor Satisfaction at Telagah Kumpe Cilongok Tourist Destination - Indra Saputra; Sugeng Rianto (International Journal of Management and Business, 2025)
This study aims to examine the destination image, tourist attractions, facilities, service quality, and promotion on visitor satisfaction. The method used is a quantitative approach with descriptive analysis techniques. Purposive Sampling, involving 220 samples. Data were obtained through questionnaire distribution and analyzed using Smart PLS V.4.1. The results of the study showed that: (1) destination image has a positive effect on visitor satisfaction, (2) tourist attractions have a positive effect on visitor satisfaction, (3) facilities do not have an effect on visitor satisfaction, (4) service quality has a positive effect on visitor satisfaction, (5) promotion has a positive effect on visitor satisfaction. This study concludes that destination image, tourist attractions, service quality, and promotions have a positive effect on visitor satisfaction at Telaga Kumpe, while facilities were not shown to have a significant effect. This means that tourist satisfaction is largely determined by how the destination is perceived, the attractions offered, the services provided, and the promotional strategies employed